Pengenalan Konsep Fonemik Dasar dalam Pembelajaran Bahasa Indonesia di SD - Annisa Fauzi (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2025)
The introduction of basic phonemic concepts in Indonesian language learning at the elementary school level is a crucial component of the language learning process. Phonemic awareness refers to the ability to recognize and distinguish the smallest units of sound in language, which are phonemes. This study aims to analyze the implementation of phonemic methods in enhancing students’ reading and writing skills in elementary schools. Through a literature review, it was found that phonemic recognition strengthens fundamental language skills, particularly in the areas of early reading and language structure mastery. The results indicate that effective phonemic learning positively influences students' literacy development, enhances their phonemic awareness, and facilitates the mastery of the Indonesian language skills at the elementary school level.